Wong's nursing care of infants and children - Hockenberry, Marilyn J.; Wilson, David (St. Louis, Missouri : Elsevier, 2015)
The leading text in pediatric nursing, Wong's Nursing Care of Infants and Children takes a unique, easy-to-understand developmental approach to describe the care of children at each age and stage of development. Childhood diseases and disorders are organized by age groups and body systems, and described through the nursing process framework. This edition includes updates on topics such as the new CPR guidelines, immunizations, and pain assessment and management. Written by pediatric experts, Dr. Marilyn Hockenberry and David Wilson, each with nearly 30 years of hands-on experience, this bestseller provides an evidence-based, clinical perspective that shows how the quality of nursing care can impact quality patient outcomes. -- Provided by publisher
UNIT I: Children, Their Families and The Nurse -- UNIT II: Childhood and Family Assessment -- UNIT III: Family-Centered Care of the Newborn -- UNIT IV: Family-Centered Care of the Infant -- UNIT V: Family-Centered Care of the Toddler and Preschooler -- UNIT VI: Family-Centered Care of the School-Age Child -- UNIT VII: Family-Centered Care of the Adolescent -- UNIT VIII: Family-Centered Care of the Child with Special Needs -- UNIT IX: The Child who is Hospitalized -- UNIT X: Childhood Nutrition and Elimination Problems -- UNIT XI: Childhood Oxygenation Problems -- UNIT XII: Childhood Blood Production and Circulation Problems -- UNIT XIII: Childhood Regulatory Problems -- UNIT XIV: Childhood Physical Mobility Problems
Includes bibliographic references and index.
Keywords: PEDIATRIC NURSING